2003
DOI: 10.1034/j.1399-6576.2003.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

A practice survey on vasopressor and inotropic drug therapy in Scandinavian intensive care units

Abstract: Background: This practice survey was performed to analyse the indications for use of vasopressor/inotropic drugs, preferred drugs and doses as well as concomitant monitoring and desired haemodynamic target values in Scandinavian ICUs. An internet‐based reporting system was implemented.Methods: A total of 223 ICUs were identified in the Scandinavian countries and invited to participate in a one‐day point‐prevalence study. An internet‐based database was constructed and a practice survey protocol designed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 17 publications
2
26
1
Order By: Relevance
“…Our data support two previous surveys that indicate that blood products are used for resuscitation in Scandinavian ICUs. 9,13 In the present study, the administration of RBCs, plasma and platelets was not associated with outcome. The two trials randomising septic patients to different RBC transfusion strategies have showed divergent results.…”
Section: S Carlsen and A Pernercontrasting
confidence: 40%
See 1 more Smart Citation
“…Our data support two previous surveys that indicate that blood products are used for resuscitation in Scandinavian ICUs. 9,13 In the present study, the administration of RBCs, plasma and platelets was not associated with outcome. The two trials randomising septic patients to different RBC transfusion strategies have showed divergent results.…”
Section: S Carlsen and A Pernercontrasting
confidence: 40%
“…Our results are also supported by previous Scandinavian data showing preference for HES 130/0.4 for ICU patients 9 and the use of a combination of colloids, crystalloids and blood products in shock patients. 13 The composition of resuscitation fluids for sepsis is controversial. In particular, the use of colloids is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The following interventions were recorded every day during shock: the type and volume of administered fluid, including crystalloids (isotonic NaCl, Ringer's lactate or acetate, other electrolyte solutions, or isotonic glucose); colloids (albumin, hydroxyethyl starch (HES), or dextran; gelatin was not used in the present cohort); blood products (red blood cells (RBCs), fresh frozen plasma, or platelet concentrate; blood products were included because data indicate that these are used for resuscitation in Scandinavian ICUs [9,10]); nutrition given (any nutritional product containing glucose of greater than 5%, amino acids, or lipids); use of corticosteroids, invasive ventilation, or renal replacement therapy; and type and maximum dose of infused inotrope/vasopressor drugs. Dopamine doses were converted into comparable doses of norepinephrine so that 1 μg/kg per minute dopamine equaled 0.01 μg/kg per minute norepinephrine [11].…”
Section: Methodsmentioning
confidence: 99%
“…Kastrup et al 16 showed that 42% of German clinicians select epinephrine from eight drug options as the first-choice drug for adult patients with LCOS, 91% of French clinicians select dobutamine from four drug options for cardiogenic shock15 and 64% of clinicians from Scandinavia select dopamine for cardiac failure 14. The present survey probably revealed higher variability in drug use because it focussed on children and hospitals from all over Europe, and also subcategorised LCOS and evaluated stepwise treatment algorithms without limiting drug choices.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the EuLoCOS-Paed questionnaire was guided by previous surveys on vasoactive drug use in adult patients1416 and guidelines on cardiac and circulatory failure in adult and paediatric care 5 6 17 18. Standard survey methods for mail and web-based surveys were also adopted to increase the overall response rate 19 20…”
Section: Methodsmentioning
confidence: 99%